Taking sides ; - Slife , Brent (McGrawHill, 2010)
Critical thinking skills are a significant component of a meaningful education, and this book is specifically designed to stimulate critical thinking and initiate lively and informed dialogue on psychological issues. In this book I present 34 selections, arranged in pro and con pairs, that address a total of 17 different controversial issues in psychology.